How Children’s Mentalistic Theory Widens their Conception of Pictorial Possibilities - Gilli, Gabriella M.; Ruggi, Simona; Gatti, Monica; Freeman, Norman H. (Frontiers in Psychology, 2016)
An interpretative theory of mind enables young children to grasp that people fulfill varying intentions when making pictures. We tested the hypothesis that in middle childhood a unifunctional conception of artists’ intention to produce a picture widens to include artists’ intention to display their pictures to others. Children aged between 5 and 10 years viewed a brief video of an artist deliberately hiding her picture but her intention was thwarted when her picture was discovered and displayed. By 8 years of age children were almost unanimous that a picture-producer without an intention to show her work to others cannot be considered to be an artist. Further exploratory studies centered on aspects of picture-display involving normal public display as well as the contrary intentions of hiding an original picture and of deceitfully displaying a forgery. Interviews suggested that the concept of exhibition widened to take others’ minds into account viewers’ critical judgments and effects of forgeries on viewers’ minds. The approach of interpolating probes of typical possibilities between atypical intentions generated evidence that in middle childhood the foundations are laid for a conception of communication between artists’ minds and viewers’ minds via pictorial display. The combination of hypothesis-testing and exploratory opening-up of the area generates a new testable hypothesis about how an increasingly mentalistic approach enables children to understand diverse possibilities in the pictorial domain.